(3GdEQTGO Edi egeGJ Yde GdESfGOs - (3TGg hdj Gddg , CMeO Hf YHO GdQMje GdaGQhbj GdOgdhj, CHh YHO GdYRjR,J (B1176 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi NU gPg GdGeI GdeQMheI HaVjdI YXjeI gi MaX GdGSfGO CeG HYO ajbhd CMeO GdeYQha Hhdi Gddg Hf YHO GdQMje GdOgdhi gPg QSGdI eSeGg HGdGQTGO Edi egeGJ Yde GdGSfGO MOGfi Edi JCdjagG GMJjGL Ggd GdYUQ Edi eKdgG s
(3BNQgG (B:s
(3hGeG GdJQZjH hGdJQYjH aQhGg GdOejGWi Yf eDdag GdMGaX Rci GdOjf YHO GdYXje Hf YHO Gdbhi GdefPQi hGeG GdeNJGQ ddMGaX Rci GdOjf YHO GdYXje Hf YHO Gdbhi GdefPQi hGeG GdeNJGQ ddMGaX VjGA GdOjf eMeO GdebOSi aQhGg GHf GdHNGQi Yf Yeg GdeDda hdjcf gPG Gs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B272s
(3eUOQ GbJfGA GdCUd (B:s
(3GdSYjOjI GdYGeI HJfhd (B((3GUhd GdMOjK (B39) s
Keywords: (3GdMOjK h GdeUWdMs